Parents’ perception of water safety and drowning risk for their children in Selangor - Mohamed Yunus, Nur Azmina; Zid, Azlina; Ab. Aziz, Mohd Noorazlan; Rajli, Mohammad Adzly; Abu Hassan Asari, Fadli Fizari (Faculty of Sports Science and Recreation, 2025)
Drowning is a major public health concern, particularly among children. This study investigated parents' perceptions of water safety and the drowning risks their children face in Selangor. A total of 70 parents at the UiTM swimming pool were selected for this study. Descriptive statistics and Pearson correlation analysis were used to analyze parents' perceptions and their relationships with drowning risk. The study examined parent’s perceptions of water safety, drowning risk and the relationship between these factors. The results showed that parents at UiTM swimming pool highly rated swimming skills and early swimming education as protective measures against drowning. For water safety perception, swimming ability had the highest mean score (M=3.98, SD=.534), while the role of supervision had the lowest score (M=3.66, SD=.624). Regarding drowning risk perception, the benefits of swimming received the highest mean score (M=4.64, SD = .430), with perceived barriers scoring the lowest (M=4.00, SD = .443). However, there were mixed responses regarding constant supervision. Moreover, a moderate positive correlation (r = .512, p < .001) was found between parents’ perceptions of water safety and drowning risk. These findings underscore the need for comprehensive water safety education programs addressing skill development and risk awareness.